ANALISIS PENDUDUK MISKIN DI SUMATERA UTARA PERIODE 2015-2020 DENGAN MENGGUNAKAN METODE ANALISIS TREND - Putri , Tisyandha; Riana br Bangun, Emi; Azmi, Nadiah; Annis, Annisa (PT. ANAN PUBLISHER CENDEKIA, 2024)
Poverty is a timeless issue, and this reality underscores why poverty always garners significant attention and sparks debate. Regardless of the ongoing controversies surrounding the concept of poverty, its eradication must be urgently addressed, and every policy made should favor the poor who desperately need attention from all parties. Poverty occurs due to the low standard of living of poor people, which results in poor life expectancy and education, thereby reducing their economic productivity. Often, the issue of poverty arises alongside the issue of unemployment. These two problems are closely related to the quality of the Human Development Index. The aim of this study is to understand the poverty of the population in North Sumatra for the period 2015-2020. The method used in this study is a quantitative method. The data collection technique used in this study involves secondary data sourced from the Central Bureau of Statistics (BPS).